Productivity of maize (Zea mays) under different crop sequences and irrigation regimes - KAUR, NAVNEET; VASHIST, KRISHAN KUMAR; BRAR, A S (The Indian Journal of Agricultural Sciences, 2021)
A two year field experiment was conducted at Research farm of Department of Agronomy, Punjab Agricultural University, Ludhiana during kharif 2016 and kharif 2017. The experiment was laid out in split-plot design with seven maize (Zea mays L.) based crop sequences, viz. maize-wheat, maize-potato-mentha + onion, maize + cowpea (f)- potato-mentha + onion, maize + cowpea (f)-potato-spring maize, maize + cowpea (f)-gobhi sarson-summer moong, maize-toria + gobhi sarson-summer moong and maize + cowpea (f)-toria + gobhi sarson-summer moong in main plots and four irrigation schedules of 0.75 IW/CPE, 1.0 IW/CPE, 1.25 IW/CPE and recommended schedule in sub plots replicated thrice. Intercropping of cowpea with maize increased the grain yield, crop and water productivity, energy output and net returns of kharif maize. The maximum grain yield of maize was recorded under recommended schedule which was statistically at par with 1.25 IW/CPE irrigation regime. Irrigation regime of 1.0 IW/CPE recorded the highest apparent water productivity with 3.00 and 3.07 kg/m3 during 2016 and 2017, respectively. Irrigation regimes of I1.25 and IRec were the most energy efficient and energy productive.